PENGEMBANGAN POTENSI WISATA PANTAI LASIANA SEBAGAI PARIWISATA BERKELANJUTAN DI KOTA KUPANG, PROVINSI NUSA TENGGARA TIMUR - Syull Rosli Sanam; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2014)
Abstract Lasiana beach is one of beach in the Lasiana village, subdistrict of Kelapa Lima, Kupang city, Province East Nusa Tenggara. This beach have interesting natural potency to developed as a very attractive natural potential to be developed as a leading tourist attraction, it has a very beautiful natural scenery with white sandy beaches characteristics, smooth and has a long coastline, the waves are calm, beautiful natural panoramic sunset and the shade of trees on the coast to offer a special attraction for tourists. Lasiana beach managed by the Department of Culture and Tourism of Kupang with the procurement of various facilities. Given the development of tourist sites Lasiana Beach is not optimal, it is necessary that efforts be constructive to improve the welfare of the community, promoting culture, nature conservation and other resources. Several attempts to do in optimizing the development of tourist sites Lasiana Beach towards sustainable tourism.